Non-financial enterprises’ shadow lending and SME survival: the role of spatial spillovers in regional financial stability - Wang, Chen; Zhang, Wei; Meng, Yongqiang; Xiong, Xiong (Frontiers in Physics, 2025)
This study examines the impact of non-financial enterprises’ shadow lending activities on the survival of small and micro enterprises (SMEs) in China. Utilizing panel data from 243 prefecture-level cities from 2012 to 2021 and applying the Spatial Durbin Model (SDM), we explore both direct and spatial spillover effects of shadow lending on SME mortality. Our empirical findings suggest that non-financial enterprises’ shadow lending significantly reduces the local SME mortality rate, while spatial econometric analysis reveals positive spillover effects, whereby shadow lending in one region enhances SME survival in neighboring areas through cross-regional financial linkages. Heterogeneity analyses indicate that these effects are more prominent in the economically developed southeastern regions, while being relatively weaker in less-developed northwestern areas, reflecting disparities in financial accessibility. Robustness checks and lagged effect analyses confirm the consistency and persistence of our findings. While shadow banking improves SME resilience through regional transmission, it may also carry potential financial risks. This study innovatively focuses on the spatial spillover effects of shadow lending by non-financial enterprises on SME survival, an area largely overlooked by previous studies. By integrating spatial econometric analysis and examining systemic vulnerabilities, this paper provides new insights into the regional complexity of informal finance.